Nonclassical titanocene silyl hydrides. - Ignatov, S; Rees, N; Tyrrell, B; Dubberley, SR; Razuvaev, A; Mountford, P; Nikonov, G (2004)
The titanocene silyl hydride complexes [Ti(Cp)2(PMe3)(H)(SiR3)] [SiR3=SiMePhCl (6), SiPh2Cl (7), SiMeCl2 (8), SiCl3 (9)] were prepared by HSiR3 addition to [Ti(Cp)2(PMe3)2] and were studied by NMR and IR spectroscopy, X-ray diffraction (for 6, 8, and 9), and DFT calculations. Spectroscopic and structural data established that these complexes exhibit nonclassical Ti-H-Si-Cl interligand hypervalent interactions. In particular, the observation of silicon-hydride coupling constants J(Si,H) in 6-9 in the range 22-40 Hz, the signs of which we found to be negative for 8 and 9, is conclusive evidence of the presence of a direct Si-H bond. The analogous reaction of [Ti(Cp)2(PMe3)2] with HSi(OEt)3 does not afford the expected classical silyl hydride complex [Ti(Cp)2(PMe3)(H)[Si(OEt)3]], and instead NMR-silent titanium (apparently TiIII) complex(es) and the silane redistribution product Si(OEt)4 are formed. The structural data and DFT calculations for the compounds [Ti(Cp)2(PMe3)(H)(SiR3)] show that the strength of interligand hypervalent interactions in the chlorosilyl complexes decreases as the number of chloro groups on silicon increases. However, in the absence of an Si-bound electron-withdrawing group trans to the Si-H moiety, a silane sigma complex is formed, characterized by a long Ti-Si bond of 2.658 A and short Si-H contact of 1.840 A in the model complex [Ti(Cp)2(PMe3)(H)(SiMe3)]. Both the silane sigma complexes and silyl hydride complexes with interligand hypervalent interactions exhibit bond paths between the silicon and hydride atoms in Atoms in Molecules (AIM) studies. To date a classical titanocene phosphane silyl hydride complex without any Si-H interaction has not been observed, and therefore titanocene silyl hydrides are, depending on the nature of the R groups on Si, either silane sigma complexes or compounds with an interligand hypervalent interaction.